Robert J. Walker : The History and Archaeology of a U.S. Coast Survey Steamship - Delgado, James P.; Nagiewicz, Stephen D. (Book collections on Project MUSE., 2020)
"This book tells the story of the steamship Robert J. Walker, a coastal survey ship that sank with loss of 21 crew off the coast of New Jersey in 1860. Leaders in the efforts to document the shipwreck describe the history of the ship and the archaeology of the wreck, emphasizing the collaborative community participation that made the project successful"--